Clinical trial evaluating apomorphine oromucosal solution in Parkinson's disease patients - Eva Thijssen; Bert Tuk; Michel Cakici; Veerle vanVelze; Erica Klaassen; Frans Merkus; Teus vanLaar; Philip Kremer; Geert Jan Groeneveld (Clinical and Translational Science, 2024)
Abstract Apomorphine, used to treat OFF episodes in patients with Parkinson's disease (PD), is typically administered via subcutaneous injections. Administration of an oromucosal solution could offer a non‐invasive and user‐friendly alternative. This two‐part clinical study evaluated the safety, tolerability, pharmacokinetics (PK), and dose proportionality of a novel apomorphine hydrochloride oromucosal solution, as well as its relative bioavailability to subcutaneous apomorphine injection and apomorphine sublingual film. In part A of the study, 12 patients with PD received 2 mg oromucosal apomorphine (4% weight/volume) and 2 mg subcutaneous apomorphine in a randomized order, followed by 4 and 8 mg oromucosal apomorphine. In part B of the study, 13 patients with PD received 7 mg oromucosal apomorphine (7% weight/volume) and 30 mg sublingual apomorphine in a randomized order, followed by 14 mg oromucosal apomorphine. Washout between dose administrations in both study parts was at least 2 days. Safety, tolerability, and PK were assessed pre‐ and post‐dose. Both study parts showed that oromucosal apomorphine was generally well‐tolerated. Observed side effects were typical for apomorphine administration and included asymptomatic orthostatic hypotension, yawning, fatigue, and somnolence. Oromucosal apomorphine exposure increased with dose, although less than dose proportional. The mean (SD) maximum exposure reached with 14 mg oromucosal apomorphine was 753.0 (298.6) ng*min/mL (area under the plasma concentration–time curve from zero to infinity) and 8.0 (3.3) ng/mL (maximum plasma concentration). This was comparable to exposure reached after 2 mg subcutaneous apomorphine and approximately half of the exposure observed with 30 mg sublingual apomorphine. In summary, clinically relevant plasma concentrations could be reached in PD patients without tolerability issues.